Vision‐related quality of life and visual outcomes after small‐incision lenticule extraction and laser in situ keratomileusis. Issue 10 (October 2015) - Ang, Marcus; Ho, Henrietta; Fenwick, Eva; Lamoureux, Ecosse; Htoon, Hla M.; Koh, Jane; Tan, Donald; Mehta, Jodhbir S.
Abstract : Purpose : To compare vision‐related quality of life (VRQoL) scores and clinical outcomes between small‐incision lenticule extraction and laser in situ keratomileusis (LASIK). Setting : Singapore National Eye Centre, Singapore. Design : Prospective study. Methods : Patients had small‐incision lenticule extraction using the Visumax 500 kHz femtosecond laser; or LASIK excimer ablation with the Wavelight Allegretto 400 Hz laser. Primary outcomes were 3‐month predictability, efficacy, and safety. Secondary outcomes were intraoperative experience, visual symptoms, and VRQoL (validated Quality of Life Impact of Refractive Correction [QIRC] questionnaire) in 25 a subgroup of patients in each group. Following Rasch analysis, "Functional" and "Emotional, " QIRC dimensions were analysed separately. Results : At 3 months, predictability (82.5% versus 85.3%, ±0.5 diopters attempted correction, P =.453), safety index (1.13 ± 0.19 [SD] versus 1.07 ± 0.16, P = .158), and efficacy index (0.91 ± 0.21 versus 0.97 ± 0.19; P = .002) were found when comparing small‐incision lenticule extraction (172 eyes) and LASIK (matched 688 eyes). Intraoperative experience between groups was not statistically different; visual fluctuations ( P = .020) and episodes of visual blurring ( P = .008) were greater after small‐incision lenticule extraction than after LASIK at 1 month but not at 3 months. There was no difference in "functional" (66.7 ± 15.7 versus 55.3 ± 22.2, P = .064) and "emotional" (42.7 ± 23.2 versus 37.9 ± 23.8, P = .394) QIRC dimensions between the 2 groups (25 patients in each group) at 3 months. Conclusion : The study, 3‐month predictability, safety, and VRQL scores were not statistically different between small‐incision lenticule extraction and LASIK. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.